Early determination of clopidogrel responsiveness by platelet reactivity index identifies patients at risk for cardiovascular events after myocardial infarction - Schäfer, Andreas; Flierl, Ulrike; Kössler, Jürgen; Seydelmann, Nora; Kobsar, Anna; Störk, Stefan; Bauersachs, Johann (Thrombosis and Haemostasis, 2011)
While acute myocardial infarction (MI) is associated with impaired clopidogrel responsiveness, systematic evaluation is lacking due to the inability of functional aggregation-based assays to analyse clopidogrel responsiveness in the presence of glycoprotein IIb/IIIa inhibitors. Using the P2Y12-specific, non-aggregation-based platelet-reactivity-index (PRI) we assessed clopidogrel responsiveness in patients with acute MI. Clopidogrel responsiveness was determined 24 hours (h) after loading with 600 mg clopidogrel in 54 patients with acute MI admitted for coronary intervention. A PRI > 50% was considered as suboptimal inhibition. Overall response in MI patients was suboptimal with a median PRI of 58%. Diabetes, low high-density lipoprotein and pre-hospital clopidogrel loading were associated with impaired clopidogrel responsiveness. Patients loaded at first medical contact had a significantly weaker platelet inhibition by clopidogrel after 24 h (PRI 63%) compared to those loaded peri-interventionally (PRI 54%, p=0.014). Clinical outcome was assessed as a combination of cardiac death, non-fatal MI, stent thrombosis, ischaemic stroke, and urgent target vessel revascularisation after 12 months. The pre-selected cut-off of PRI ≤ 50% yielded a sensitivity of 87% at a specificity of 26%, whereas a PRI ≤ 57% determined by receiver-operating characteristics (ROC)-analysis yielded a sensitivity of 80% at a specificity of 56% (event rate: PRI ≤ 57%: 12.0%; PRI > 57%: 41.4%, p=0.0136). In conclusion, PRI detects clopidogrel responsiveness in acute MI patients requiring glycoprotein IIb/IIIa antagonism; and impaired clopidogrel responsiveness predisposes to clinical events. Pre-hospital clopidogrel loading was associated with impaired response and more adverse events challenging the concept of earliest oral clopidogrel loading in MI patients.
Keywords: ADP receptors; platelet activation; diabetes; P2Y12; myocardial infarction